Medium- and long-term recurrence after radioiodine therapy for differentiated thyroid carcinoma with recombinant human thyrotropin: a meta-analysis - Yao, Qixian; Song, Lili; Xu, Jun; Wu, Zhongliang (Frontiers in Endocrinology, 2024)
IntroductionRadioactive iodine (RAI) is commonly used in the management of differentiated thyroid cancers (DTCs). However, the long-term efficacy and the risk of tumor recurrence associated with it remain unclear. In particular, the comparison between recombinant human thyrotropin (rhTSH) and thyroid hormone withdrawal (THW) in terms of medium- and long-term recurrence rate in DTC patients has not been fully elucidated.MethodsA systematic search was carried out to identify articles comparing medium- and long-term outcomes (> 2 years) based on treatment with either rhTSH or THW. Ten studies, consisting of six randomized controlled trials (RCTs) and four retrospective studies with a total of 2,833 patients, were included in the analysis.ResultsThere was no significant difference in the medium- and long-term recurrence rates between the rhTSH group and the THW group. This was also the case in subgroup analyses of only RCTs or only retrospective studies. The structural incomplete response (SIR) rate was slightly higher in the rhTSH group, but a subgroup analysis of RCTs alone showed no significant difference in SIR between the two groups.DiscussionrhTSH is comparable to THW in achieving successful ablation of residual disease and maintaining low recurrence rates. However, further RCTs are required to investigate whether rhTSH can increase the risk of SIR.